Aerial Interpretation of Muskeg: A Critical Analysis of Form Features in the Canadian Muskeg Complex - Korpijaakko, Erkki (My University, 1970)
The ontogeny of a specific high altitude (30,000') airform pattern was investigated. The possibilities of using this pattern, and certain related phenomena which appear with it,for sub-surface ice prediction was demonstrated. For the purpose of laying out the general background of the controls of paludification, as they affect indirectly the pattern development, a rather detailed account of the geomorphology, geology and climate of the study areas was given. The summaries of these accounts demonstrate their effect on pattern evolution. These background data as a foundation for a more specific account of the developmental processes of the airform pattern were given as based on abiotic and biotic interplay in the development. Finally in order to demonstrate universal application of aerial interpretation of muskeg a brief comparison of the analogous conditions of paludification and pattern in Finnish and Canadian muskeg was given.
Aerial Interpretation of Muskeg
This thesis is missing page 355 which is not in any other copy of the thesis. -Digitization Centre
Keywords: muskeg; canadian muskeg complex; aerial interpretation; form feature